Entangled objects exchange, material culture, and colonialism in the Pacific - Thomas, Nicholas 1960- (Harvard University Press, 2009)
Entangled Objects threatens to dislodge the cornerstone of Western anthropology by rendering permanently problematic the idea of reciprocity. All traffic, and commerce, whether economic or intellectual, between Western anthropologists and the rest of the world, is predicated upon the possibility of establishing reciprocal relations between the West and the indigenous peoples it has colonized for centuries